2006
DOI: 10.1177/1062860606294631
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Central Line-Associated Bloodstream Infections

Abstract: Hospital-acquired infections add considerable morbidity and mortality to patient care. However, a detailed economic analysis of these infections on an individual case basis has been lacking. The authors examined both the hospital revenues and expenses in 54 cases of patients with central line-associated bloodstream infections (CLABs) over 3 years in 2 intensive care units and compared these financial data with patients who were matched for age, severity of illness on admission, and principal diagnosis. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 11 publications
(17 reference statements)
0
34
0
Order By: Relevance
“…1 Annually there are about 15 million central vascular catheter-days, 50,000 patients with CLABSIs, and nearly 15,000 CLABSIrelated deaths in the United States, with health care costs in the range of $25,000 to $83,500 per patient. [2][3][4][5][6][7] Education and training of health care providers feature prominently in the CLABSI prevention guidelines published by the Centers for Disease Control and Prevention (CDC). 5 Simulation-based training for the placement of central venous catheters (CVCs) is superior to the apprenticeship model ("see one, do one, teach one"), [8][9][10] is associated with reduction in CLABSI rates, 8,11 and is likely to reduce intensive care unit (ICU) costs.…”
mentioning
confidence: 99%
“…1 Annually there are about 15 million central vascular catheter-days, 50,000 patients with CLABSIs, and nearly 15,000 CLABSIrelated deaths in the United States, with health care costs in the range of $25,000 to $83,500 per patient. [2][3][4][5][6][7] Education and training of health care providers feature prominently in the CLABSI prevention guidelines published by the Centers for Disease Control and Prevention (CDC). 5 Simulation-based training for the placement of central venous catheters (CVCs) is superior to the apprenticeship model ("see one, do one, teach one"), [8][9][10] is associated with reduction in CLABSI rates, 8,11 and is likely to reduce intensive care unit (ICU) costs.…”
mentioning
confidence: 99%
“…1,2 The Joint Commission defines CLABSI as "a primary bloodstream infection (that is, there is no apparent infection at another site) that develops in a patient with a central line in place within the 48-hour period before onset of the bloodstream infection that is not related to infection at another site." 3 Published estimates of attributable costs of CLABSI in adult patients have varied over years and across hospital settings, 4,5 with 2010 estimates of $50 094 per event from 1 tertiary care, academic medical center. 6 A pediatric study found an attributable 2008 dollar cost of $33 039 per CLABSI in a sample of 22 critically ill children.…”
mentioning
confidence: 99%
“…One CLABSI is estimated to prolong a patient's hospitalization by an average of 7 days with an estimated cost of between $3700 and $29 000 1 ; a more recent study found that excess costs due to CLABSI were $26 839. 2 In addition, the mortality rate associated with a CLABSI is approximately 18%. About 14 000 to 28 000 deaths occur annually due to central line infections.…”
Section: Resultsmentioning
confidence: 99%